ECONOMIC INTERACTIVE SPACE: AN ADAPTATION OF COMMUNITY RESILIENCE MECHANISM IN AN ENCLAVE SETTLEMENT - Mohammad Ischak; Bambang Setioko; Dedes Nur Gandarum (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2018)
Abstract The rapid urban growth at the periphery area developed by residential developers impacted on the socio-spatial segregation between new and pre-existing indigenous settlements. One phenomenon is that many indigenous settlements are enclaved in the new settlement area. Changes in landscape and environment around indigeneus settlement are occured as a result of a pressure. It is the main factor for suddened changes in the pattern of livelihood of enclaved settlement inhabitants. This article is intended to explain the findings on how the inhabitants of enclaved settlement respond and survive to these changes and pressures in the spatial context. The study employed descriptive analysis method by observing the characteristics of settlements by focusing on the quality of inhabitants’ life related to the spatial changes and segregations phenomena. The results of the study highlight that the spatial changes and the survival community are a form of adaptation procces to get economic benefit by making changes to their lands or buildings because of the residential development in its sorrounding. These phenomena resulted in the emergence of economic interactive space in the specific spatial arrangement. Keywords: enclaved settlements, economic interactive space, adaptation